Pengaruh Kecerdasan Emosional dan Kemandirian Belajar terhadap Prestasi Belajar Mata Pelajaran Ekonomi Siswa Kelas XII SMA Negeri 33 Jakarta - Maya Dhia Fathiyah; Oda Rahma; Siti Aminah (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to determine the significant effect of emotional intelligence and learning independence on learning achievement in economics subjects. This study used 60 samples from class XII SMA Negeri 33 Jakarta, using a quantitative approach with quantitative research methods through questionnaire research instruments, library research and field research such as surveys, interviews, direct observations in schools. The results of the analysis prerequisite test show that all variables meet the requirements, and based on the results of this study it can be concluded that there is a significant influence of emotional intelligence on learning achievement with the acquisition of Sig. 0.000 <0.05 contribution of 21.27% and there is a significant effect of learning independence on learning achievement with the acquisition of Sig. 0.000 < 0.05 contribution of 49.9%. In this study, there is a correlation between variables and simultaneously emotional intelligence and learning independence affect student learning achievement. Researchers suggest that students are better able to get used to being independent in learning, independent in the sense of being able to find various sources of information or knowledge from several sources of knowledge not only from one economics teacher at school.